Professional identity development of Flemish occupational therapists: A narrative study - Ellen Claessens; Sofia Vikström; Michael P. Sy (Taylor & Francis Group, 2024)
Background A less developed professional identity negatively influences a person's mental well-being and is suggested to potentially affect quality of care and thus clients' well-being. Literature indicates that a strong developed professional identity is to strive for. In Flanders, Belgium, cultural and legislative challenges negatively impact the professional development of occupational therapists.Aim/objectives To explore the professional identity development of Flemish occupational therapists, with a focus on significant events shaped by aspects of self-efficacy.Method Five Flemish occupational therapists were interviewed twice. The semi-structured and open follow-up interviews were all conducted online. Data was analysed by using a narrative- and narrative slopes analysis.Results Similar and unique experiences emerged: occupational therapy appeared as an unexpected career choice, clinical placements were important, getting and staying in the work field has its challenges, and continuously improving themselves. Self-efficacy fluctuated during their whole journey.Conclusion Five unique narratives, raise awareness of potentially vulnerable events in becoming an occupational therapist.Significance This study highlights the importance of actively reflecting on how to support students, novice, and senior therapists in developing and nurturing their professional identity (e.g. continued professional development, strong supervisor relationship, interprofessional education).